Formulation Development and Evaluation of Nanofibers Containing Antifungal Drug using Electrospining Technique for the Treatment of Oral Candidacies - Mirgane, Aboli A.; Borkar, Smita P; Shinde, Snehal M; More , Priti U (Asian Journal of Pharmaceutical Research and Development, 2024)
Oral Candidiasis is common disease caused due to overgrowth of Candida albicans. To treat this type of infection different dosage forms are marketed. The purpose behind this research is to provide knowledge about nanofibers as a novel drug delivery for the treatment of oral candidiasis. For the formulation of nanofibers electrospinning technique was used. To determine the effectiveness of nanofiber drug delivery evaluation was done.